PERPADUAN METODE QUEUE TREE DAN FL7 DALAM EFISIENSI PENGGUNAAN BANDWIDTH BERBASIS ROUTER - Aulia Ichsan; Muhammad Zulfansyuri Siambaton (Deli Sains Informatika, 2022)
The availability of internet bandwidth management on the UISU campus is considered necessary for further design, because the available bandwidth management has a simple concept and the use of bandwidth is deemed to be more efficient. Some of the impacts are that the distribution of bandwidth is not more structured (each client does not have a definite bandwidth guarantee when the number of bandwidth users/traffic is dense, fellow internet users overlap each other resulting in a tendency to gain more bandwidth on certain clients only (not equally), pattern filtering data such as streaming traffic or certain websites are easy to access, resulting in no opportunity to save bandwidth usage. The solutions for some of these indications have been carried out by previous researchers but are not efficient enough if applied to large campus networks such as UISU. Therefore this research will develop using a combination of methods, namely Queue Tree by utilizing traffic priority, Commited Information Rate/Maximum Information Rate and the FL7 method to define certain data patterns in the text url so that the use of bandwidth availability is more efficient. using the average value parameter (avg rate) using a mikrotik OS router and packet ICMP parameters using throughput, delay, jitter and packet loss. Keywords: The combination of Queue Tree and FL7 methods; bandwidth efficiency; parameter.